Use of “ARRIAH-AviFluVac” vaccine in turkeys, geese and ducks - N. V. Moroz; S. V. Frolov; V. N. Irza; L. O. Scherbakova; V. Yu. Kulakov (Ветеринария сегодня)
“ARRIAH-AviFluVac” vaccine against H5 avian influenza was demonstrated to be effective for  ducks, geese and turkeys both in the laboratory and production environment. When administered to ducks at 0.5; 1.0 and 1.5 cm3, the vaccine provided 100%-effective protection of birds against the disease and death after challenge with the relevant high pathogenicity avian influenza virus of subtype H5N1, clade 2.3.4.4b. Singular 0.5–1.5 cm3 inoculation induced formation of antibodies, which were detected in the hemagglutination inhibition test at the titres that ranged from 4.3 to 6.1 log2. The vaccine facilitated 9–26-fold decrease in the virulent virus shedding by the ducks. Protection of turkeys vaccinated at the dose of 1.0 cm3 was maintained at the level of 87.5% after challenge with high pathogenicity avian influenza virus of subtype H5N1, clade 2.3.4.4b. The vaccine induced formation of antibodies at the titres of 4.9 and 5.5 log2 in turkeys after singular and double vaccination at the dose of 1.0 cm3, respectively. It was demonstrated, that after double administration of 1.0 cm3 of “ARRIAH-AviFluVac” vaccine, the post-vaccinal avian influenza antibody level exceeded 5.0 log2 in 75.9–90.0% of the geese population. The most appropriate way of the vaccine use in turkeys, ducks and geese involves at least its double administration at the double commercial dose. Higher species resistance of ducks to the challenge with avian influenza virus of subtype H5, clade 2.3.4.4bas compared to turkeys was also demonstrated.